Voices of Singapore national beach volleyball female athletes: What is an ideal coach? - Lau, E. S.; Chung, H. J.; Hwa, M. C. Y. (International Journal of Sports Science & Coaching, 2020)
A coach has a great influence on athletes` performance and development. Communication and coaching styles that work with male athletes may not be effective in female athletes. The alignment of coaching to the preferences of female athletes is important for effective coaching and their holistic development. Therefore, it is essential to understand how female athletes perceive an ideal coach. The purpose of this research is to uncover how Singapore national beach volleyball female athletes voice about an ideal coach. Seven Singapore national beach volleyball female athletes were interviewed. Thematic analysis was used to analyze the data. The three main themes are - understanding the female athletes, being a role model with responsibility, and possessing rich experience as a coach and athlete. The three main themes that were developed from the voices of the Singapore national beach volleyball female athletes are supported by the literature on transformational coaching in terms of these components: idealized influence and individualized consideration. The findings of this research could help to establish a more comfortable, trusting and well-communicated training environment for female athletes.